Analysis of Gross Regional Domestic Products that Influence the Economic Growth Of Batam City 2010 – 2020 - Angela Angela (Eduvest - Journal of Universal Studies, 2021)
Batam city which is one of the areas in Indonesia that has progressed quite rapidly, as a city located on the border between Singapore and Malaysia. Batam city has a lot of potential in developing its economy, one of which is in the industrial sector. Some of the objectives and reasons of the implementation of this research is as one of the sources of information in studying GDP from Batam, knowing how the economic growth of Batam city from year to year, and factors that affect the economic development of Batam City. In the period of 10 years, from 2010 to 2020, the growth rate of Batam city GDP is in a fairly stable position despite a slight decrease. The result of Batam GDP city every year is quite influential to the economy of batam city this can be seen from the growth rate of GDP every year although the average is below 5% but can bring significant changes to Batam.